Strategi Pengembangan Potensi Wisata Sebagai Upaya Peningkatan Eksistensi Ekowisata Dan Peningkatan Perekonomian Masyarakat - Alfiatur Rohmah; Nurus Sobakh; Etta Mamang Sangadji (Institut Citra Internasional, 2025)
Tourism has a strategic role in regional development because it can drive economic growth, create jobs, and strengthen local cultural identity. Andonosari Village, Tutur District, Pasuruan Regency, is an area with great natural and cultural tourism potential, but its development has not been optimal so that its contribution to the community's economy is still limited. This study aims to formulate a strategy for developing tourism potential to increase the existence of ecotourism while encouraging the economic growth of village communities. The focus of the research is directed at how the right strategy can link the sustainability of ecotourism with community welfare. The research method uses a qualitative phenomenological approach with subjects of village officials, Pokdarwis, tourism business actors, and community leaders. Data were collected through interviews, observations, and documentation, and analyzed through stages of reduction, presentation, and drawing conclusions. The results of the study show that ecotourism development strategies include five main aspects: strengthening village institutions and Pokdarwis, increasing human resource capacity, sustainable utilization of natural and cultural potential, digital promotion, and collaboration with the government and external stakeholders. The conclusion confirms that this strategy not only strengthens the existence of ecotourism in Andonosari Village, but also improves the community's economy through increasing residents' income, opening new job opportunities, and developing local MSMEs.